Population dynamics of roundjaw bonefish Albula glossodonta at a remote coralline Atoll inform community‐based management in an artisanal fishery. (25th November 2019) - Filous, Alexander; Lennox, Robert J.; Eveson, Paige; Raveino, Raphael; Clua, Eric E. G.; Cooke, Steven J.; Danylchuk, Andy J.
Abstract: Fisheries management requires knowledge on the population dynamics of exploited stocks. To that end, the present study used a mark–recapture approach to characterise the population demographics of roundjaw bonefish Albula glossodonta (Forsskål) and their interaction with a data‐limited fishery on Anaa Atoll in the Tuamotu Archipelago of French Polynesia. Over the course of the study, 2, 509 bonefish were tagged and 12.3% were recaptured. The L ∞ of bonefish was estimated at 71 cm fork length (FL) with a K of 0.17, based on changes in FL between capture events. Artisanal fish traps located in the migratory corridors of the atoll accounted for 94% of recaptures and these movements occurred during the waning moon. Fishing mortality increased as bonefish reach sexual maturity, recruiting to the trap fishery at age 4 with the onset of spawning behaviour. Bonefish abundance between ages 3 and 5 was estimated to be 29, 079 individuals. This case study demonstrated the utility of mark–recapture in filling knowledge gaps that impede the management of data‐limited fisheries. Ultimately, these results supported the creation of an Educational Managed Marine Area and the resurgence of rahui (seasonal closure) to manage this fishery.